Long-Term Results after Fallot Repair - Kleinöder, Jonas; Purbojo, Ariawan; Blumauer, Robert; Cuomo, Michela; Alkassar, Muhannad; Dittrich, Sven; Cesnjevar, Robert (Thoracic and Cardiovascular Surgeon, 2022)
Background The aim of this study was to evaluate the long-term outcome and freedom from pulmonary valve replacement (PVR) after initial repair of tetralogy of Fallot (TOF). Patients and Methods The cohort of 306 patients treated between 1980 and 2017 was divided into anatomical subgroups according to the diagnosis of TOF-pulmonary stenosis, TOF-pulmonary atresia and TOF-double outlet right ventricle. Patients were treated with transannular patch (TAP), valve sparing repair (VSR), or conduits from the right ventricle to the pulmonary arteries (RVPA conduits). Results There were 21 deaths (6.9%), 14 being hospital deaths (4.6%) after primary correction and four deaths (1.3%) occurred after PVR. One patient died after a non-cardiac operation (0.3%). There were two late deaths (0.7%). During the past 12 years no early mortality has been observed. Ninety-one patients (30.4%) received PVR after a median of 12.1 +/- 7.0 years with an early mortality of 4.4% ( n = 4) and no late mortality. A significant difference in freedom from reoperation after TAP, VSR, and RVPA-conduits could be identified. Multivariate analysis displayed transannular repair ( p = 0.016), primary palliation ( p <0.001), the presence of major aortopulmonary collateral arteries (MAPCA; p = 0.023), and pulmonary valve Z -scores < - 4.0 ( p = 0.040) as significant risk factors for PVR. Conclusion TOF repair has a beneficial long-term prognosis with low morbidity and mortality. Pulmonary valve Z -scores < - 4.0, transannular repair, and presence of MAPCAs are associated with earlier PVR. Non-VSRs and TOF-pulmonary atresia lead to earlier reoperation but have no negative impact on survival.
CRIS-Team WoS Importer:2022-07-29

The Father’s Part: A Pilot Evaluation of a Father-Centered Family Intervention Group in Child and Adolescent Psychiatry - Mestermann, Stefan; Kleinöder, Jonas; Arndt, Marie; Krämer, Josef; Eichler, Anna; Kratz, Oliver (Behavioral Sciences, 2024)
Changes in parental roles have renewed the focus on a father’s involvement in an offspring’s psychological development. However, fathers are still under-represented in family research. There are only a few structured father-centered intervention programs in child and adolescent psychiatry. In a German population sample, a pilot father-centered family intervention program with n = 16 participants, conducted in person (n = 8) and online (n = 8), in a child and adolescent psychiatry inpatient/day clinic setting was evaluated by comparing paternal stress, PSE, and child-rated paternal competence in a pre–post design. Participating fathers showed significant decreases in child-related parenting stress (presence: p = 0.042, online: p = 0.047) and significant increases in PSE (p = 0.006/0.012). Parent-related stress and child-rated paternal competence were unaffected (p = 0.108/0.171; p = 0.167/0.101), while small-to-medium effect size measures pointed in the direction of our hypothesis (d = 0.48/0.36; d = 0.37/0.50). Participant satisfaction was higher in person than online (p = 0.008). As social and biological fathers have important influences on child and adolescent well-being and development, they should be included more frequently in prevention and intervention programs. Fathers seem to benefit from gender-specific intervention programs with regard to stress reduction, as well as experiencing competence- and PSE-increasing effects.
CRIS-Team Scopus Importer:2024-03-08
Keywords: child development; parent-centered interventions; parental behavior; parenting stress; parent–child-relation

The impact of early surgical ventricular septal defect repair on parenting behavior and mother-child relationship: a prospective longitudinal study - Hemetsberger, Jonas; Mestermann, Stefan; Nicol, Hannah; Purbojo, Ariawan; Cesnjevar, Robert A.; Kratz, Oliver; Eichler, Anna; Gerlach, Jennifer (Frontiers in Pediatrics, 2024)
Introduction: Many studies have investigated the impact of congenital heart defects (CHD) on child development. However, because CHD not only affects the child and his or her development but, also the entire family, family functioning after pediatric cardiac surgery is of increasing research interest. This prospective childhood-adolescence case-control study aimed to examine differences and changes in parenting behavior and mother-child relationship quality after early surgical repair of an isolated ventricular septum defect (VSD) compared to non-affected controls. Patients and methods: 39 affected children (M = 7.3 years) with surgically repaired VSD and their mothers were compared with a matched, non-affected control group of 39 mother-child-dyads (M = 7.3 years) during primary school age (t1). At child early adolescence, 24 affected children (M = 12.4 years) and 24 children of the control group (M = 13.2 years) were examined again (t2). Parenting behavior characteristics (t1: mother report; t2: mother- and child report) and mother-child relationship quality (t2: child report) were measured by standardized questionnaires. Results: The mother-rated parenting behavior dimensions Involvement (p <.001, η2p =.37), Parental Monitoring (p =.014, η2p =.17) and Corporal Punishment (p <.001, η2p =.57) significantly decreased from t1 to t2 in both cohorts. Responsible Parenting Behavior tended to decrease from t1 to t2 in the control group, while remaining stable in the VSD-group (p =.088, η2p =.09). Independent of the group, higher mother-child relationship quality was associated with more Positive Parenting Behavior (p <.001, η2p =.34), more Involvement (p =.003, η2p =.22) and fewer Inconsistency (p <.001, η2p =.31) in the child-rating; and more Positive Parenting Behavior in the mother-rating (p =.039, η2p =.10). Conclusion: VSD affected mother-child-dyads were mostly comparable in their parenting behavior characteristics and mother-child relationship quality to non-affected controls. The absence of a decrease in maternal Responsible Parenting Behavior in the VSD group may indicate challenges during the developmental task of autonomy in adolescence. Nevertheless, adaptive family functioning after early pediatric surgical VSD repair seems possible.
CRIS-Team Scopus Importer:2024-11-22
Keywords: congenital heart disease; longitudinal study; mother; mother-child relationship; parenting behavior; pediatric cardiac surgery; ventricular septal defect